Performance evaluation of crumb rubber and bio-based polyurethane compound in terms of rheological and aging properties of asphalt binder - Kok, Baha Vural; Ozdemir, Nisanur Gurcay (Elsevier Sci Ltd, 2023)
This study explored the effects of the combined use of CR and polyurethane (PU), whose use in bitumen modification is still in its infancy. The polymeric 4.40-diphenylmethane diisocyanate (MDI) and palm-oil-based polyol were used for the PU modification. A 4:1 M ratio of NCO/OH was found to be successful in forming urea bonds in the CR-modified binder. The performance of CR and CR + PU-modified bitumen was compared with the most widely used SBS modification. The binders were subjected to conventional and rheological tests. Fourier transform infrared spectroscopy was utilized to evaluate the effect of aging. The use of 8 %CR and 4% PU together provided a considerable performance improvement over the use of CR alone and that this combined binder provided better plastic deformation resistance, and low-temperature behavior than the 4 %SBS modifi-cation. The chemical reaction between PU and CR prevented the decomposition and had a significant effect on increasing the storage stability. The use of PU with CR was found to reduce chain scission, condensation and oxidation caused by aging.
Keywords: Bitumen; Crumb rubber; Polyurethane; Modification; Rheological properties